How Bank Competition Affects Firms' Access to Finance - Love, Inessa; Martínez Peria, María Soledad (World Bank, Washington, DC, 2012)
Combining multi-year, firm-level surveys with country-level panel data for 53 countries, the authors explore the impact of bank competition on firms' access to finance. They find that low competition, as measured by high values of the Lerner index, diminishes firms' access to finance, while commonly-used bank concentration measures are not robust predictors of firms' access to finance. In addition, they find that the impact of competition on access to finance depends on the environment that banks operate in. Some features of the environment, such as greater financial development and better credit information, can mitigate the damaging impact of low competition. But other characteristics, such as high government bank ownership, can exacerbate the negative effect.